Adequacy of Group Decisions as a Function of the Decision-Making Process - Holloman, Charles R.; Hendrick, Hal W. (Academy of Management Journal, 1972)
This study investigated the relative adequacy of six modes of group decision-making: (1) Averaged Decision, (2) Leader Decision, (3) Committee Decision, (4) Majority Vote, (5) Consensus, and (6) Consensus after Majority Vote. Increases in decision adequacy occur when groups use procedures which permit the direct participation of more of the group members.